2007
DOI: 10.1111/j.1741-6787.2007.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the Processes of Knowledge Transfer in Nursing

Abstract: This manuscript can contribute to our understanding of the theoretical foundations linking these concepts and these processes by comparing and contrasting them. It also shows the value and empirical importance of the cognitive and interpersonal processes of knowledge transfer by which research findings and evidence can be successfully translated and implemented into the nursing clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 77 publications
(95 reference statements)
1
34
1
3
Order By: Relevance
“…Furthermore, such interventions have to be disseminated throughout all hospital wards where patient may die. Many of these wards however lack specific palliative care expertise [16,17]. This is similar to other specific areas, such as infection control and wound and tissue care.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Furthermore, such interventions have to be disseminated throughout all hospital wards where patient may die. Many of these wards however lack specific palliative care expertise [16,17]. This is similar to other specific areas, such as infection control and wound and tissue care.…”
Section: Introductionmentioning
confidence: 80%
“…Our findings might have been affected by the high turnover rate of nurse champions and by the 5-month run-up period which might have been too short for nurse champions to prepare for their new roles before we started the postintervention assessment. A main element of the intervention is knowledge transfer; this is a complex process that implies that nurse champions first have to improve their own knowledge and then have to learn how to disseminate knowledge and skills among their colleagues in the multidisciplinary team [17][18][19]. It is suggested that nurse champions can only have an effect when they have knowledge of palliative care, teaching capacities, and authority towards managers, nurse colleagues and physicians [24,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparaison de deux méthodes de dissémination de résultats de recherche dans le domaine de la santé : les arts et le café scientifique l'accès à des opportunités de financement, la conduite de projets de recherche ciblés, etc., peu de données permettent de conclure à l'efficacité des modèles actuels d'application des connaissances (Tugwell et al, 2007 ;Aita et al, 2007 ;Grimshaw et al, 2006). Les experts de ce domaine demeurent incertains quant à ce qui influence l'adoption (ou la non-adoption) des résultats de la recherche par les utilisateurs de ces données.…”
Section: Introductionunclassified